POLÍTICA SOCIOLABORAL EN LA ARGENTINA CONTEMPORÁNEA. ALCANCES, NOVEDADES Y SALVEDADES - Grassi, Estela (Universidad de Costa Rica, 2013)
The article studies the labour policies of the Argentine State in the last decade. It shows the limits and the alternatives that emerge, since protected work (decent, according to ILO) regained a central place as the base of the social inclusion. The discordance between the labour policy and the self-employment policy is analysed, as well as the innovation that implies the policy that extends social security to informal workers (with o without a job).